background image

1. A morphism (

f

;

A

;

B

) of the category of funcoid triples is monovalued iff

the funcoid

f

is monovalued.

2. A morphism (

f

;

A

;

B

) of the category of funcoid triples is injective iff the

funcoid

f

is injective.

Theorem 41

The following statements are equivalent for a funcoid

f

:

1.

f

is monovalued.

2.

a

atoms 1

F

(Src

f

)

:

h

f

i

a

atoms 1

F

(Dst

f

)

0

F

(Dst

f

)

 

.

3.

∀I

,

J ∈

F

(Dst

f

) :

f

1

(

I ∩ J

) =

f

1

I ∩

f

1

J

.

4.

I, J

P

(Dst

f

) :

f

1

(

I

J

) =

f

1

I

f

1

J

.

Proof

(2)

(3)

Let

a

atoms 1

F

(Src

f

)

,

h

f

i

a

=

b

. Then because

b

atoms 1

F

(Dst

f

)

0

F

(Dst

f

)

 

(

I ∩ J

)

b

6

= 0

F

(Dst

f

)

⇔ I ∩

b

6

= 0

F

(Dst

f

)

∧ J ∩

b

6

= 0

F

(Dst

f

)

;

a

[

f

] (

I ∩ J

)

a

[

f

]

I ∧

a

[

f

]

J

;

(

I ∩ J

)

f

1

a

⇔ I

f

1

a

∧ J

f

1

a

;

a

f

1

(

I ∩ J

)

6

= 0

F

(Src

f

)

a

f

1

I 6

= 0

F

(Src

f

)

a

f

1

J 6

= 0

F

(Src

f

)

;

f

1

(

I ∩ J

) =

f

1

I ∩

f

1

J

.

(3)

(1)

f

1

a

f

1

b

=

f

1

(

a

b

) =

f

1

0

F

(Dst

f

)

= 0

F

(Src

f

)

for every

two distinct atomic filter objects

a

and

b

on Dst

f

. This is equivalent to

¬

(

f

1

a

[

f

]

b

);

b

≍ h

f

i

f

1

a

;

b

f

f

1

a

;

¬

(

a

f

f

1

b

). So

a

f

f

1

b

a

=

b

for every atomic filter objects

a

and

b

. This is

possible only when

f

f

1

I

FCD

(Dst

f

)

.

(4)

(3)

f

1

(

I∩J

) =

T

D

f

1

E

up(

I∩J

) =

T

D

f

1

E

{

I

J

|

I

up

I

, J

up

J }

=

T

n

f

1

(

I

J

)

|

I

up

I

, J

up

J

o

=

T

n

f

1

I

f

1

J

|

I

up

I

, J

up

J

o

=

T

n

f

1

I

|

I

up

I

o

T

n

f

1

J

|

J

up

J

o

=

f

1

I ∩

f

1

J

.

(3)

(4)

Obvious.

¬

(2)

⇒ ¬

(1)

Suppose

h

f

i

a /

atoms 1

F

(Dst

f

)

0

F

(Dst

f

)

 

for some

a

atoms

A

.

Then there exist two atomic filter objects

p

and

q

on Dst

f

such that

p

6

=

q

and

h

f

i

a

p

∧ h

f

i

a

q

. Consequently

p

6≍ h

f

i

a

;

a

6≍

f

1

p

;

a

f

1

p

;

f

f

1

p

=

h

f

i

f

1

p

⊇ h

f

i

a

q

;

f

f

1

p

*

p

and

f

f

1

p

6

= 0

F

(Dst

f

)

. So it cannot be

f

f

1

I

FCD

(Dst

f

)

.

37